US Immigration Politics, Sanctions Threats and Private Prison Corporations’ Stock Market Values - Park, Jihye (The British journal of criminology, 2023)
Although politics play pivotal roles in the emergence and operation of private prison corporations (PPCs), less is known about the effects of politics on PPCs’ financial performance. This paper examines the economic consequences of US immigration politics on PPCs using stock market data. Results show that PPCs benefit from restrictive immigration politics through increased stock values and certainty of future profitability. In contrast, their stock values are more likely to fall when the federal government announces sanctions threats on PPCs. These immigration politics only shape PPCs because of their unique business partnership with governments, but do not have meaningful impacts on private security companies that hold weak commercial interests in immigration politics. Finally, this study offers policy implications by revealing consequential effects of national-level politics on PPCs’ financial performance, suggesting future directions for federal roles in regulating PPCs.